Cardiac reinnervation affects cardiorespiratory adaptations to exercise training in individuals with heart transplantation - Ciolac, Emmanuel G [UNESP]; Castro, Rafael E; Marçal, Isabela R [UNESP]; Bacal, Fernando; Bocchi, Edimar A; Guimarães, Guilherme V (Oxford University Press (OUP), 2020)
Purpose: The purpose of this study was to investigate the hemodynamic and cardiorespiratory adaptations to exercise in individuals with heart transplantation with evidence of cardiac reinnervation (cardiac reinnervation group) versus without evidence of cardiac reinnervation (no cardiac reinnervation group). Methods: Sedentary individuals with heart transplantation (age = 45.5 ± 2.2 years; time elapsed since surgery = 6.7 ± 0.7 years) were divided into the cardiac reinnervation (n = 16) and no cardiac reinnervation (n = 17) groups according to their heart rate response to cardiopulmonary exercise testing. The 24-hour ambulatory blood pressure, carotid-femoral pulse wave velocity, and cardiorespiratory fitness were assessed before and after 12 weeks of a thrice-weekly exercise program (five minutes of warm-up, 30 min of endurance exercise, one set of 10–15 reps in five resistance exercises, and five minutes of cool-down). Results: The cardiac reinnervation group had reduced (p < 0.01) 24-hour systolic/diastolic blood pressure (7/9 mm Hg), daytime systolic/diastolic blood pressure (9/10 mm Hg) and nighttime diastolic blood pressure (6 mm Hg) after training. The no cardiac reinnervation group reduced (p < 0.05) only 24-hour (5 mm Hg), daytime (5 mm Hg) and nighttime (6 mm Hg) diastolic blood pressure after training. Hourly analysis showed that the cardiac reinnervation group reduced systolic/diastolic blood pressure for 10/21 h, while the no cardiac reinnervation group reduced systolic/diastolic blood pressure for only 3/11 h. The cardiac reinnervation group also improved both maximal oxygen consumption (10.8%) and exercise tolerance (13.4%) after training, but the no cardiac reinnervation group improved only exercise tolerance (9.9%). Pulse wave velocity did not change in both groups. Conclusion: There were greater improvements in ambulatory blood pressure and maximal oxygen consumption in the cardiac reinnervation than the no cardiac reinnervation group. These results suggest that cardiac reinnervation associates with hemodynamic and cardiorespiratory adaptations to exercise training in individuals with heart transplantation.
Keywords: Ambulatory blood pressure monitoring; arterial stiffness; autonomous nervous system; cardiac reinnervation; exercise training